2021
DOI: 10.3390/children8070575
|View full text |Cite
|
Sign up to set email alerts
|

Does Perceived Competence Mediate between Ball Skills and Children’s Physical Activity and Enjoyment?

Abstract: The major purpose of this study was to examine the potential mediating role of perceived motor skill competence on relationships between actual ball skills and children’s physical activity (PA) and PA enjoyment. A total of 294 students (Mage = 10.96 ± 0.76; 51.7% boys) from three elementary schools completed validated questionnaires assessing their perceived competence, self-reported PA, and PA enjoyment. Students’ actual ball skills (i.e., basketball, overhand throwing, striking) were measured by PE MetricsTM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…Navarro et al [51] highlighted that physical self-concept, especially the perception of physical fitness, was an essential factor for enjoyment in these classes. These perceptions are important and relevant; it has even been observed that the relationships between motor skills and the practice of PA are modulated by factors such as self-concept [52][53][54][55]. Therefore, it is possible that adolescents with adequate motor skills would not agree to engage in PA, or were not fully involved, due to a distorted perception of PA.…”
Section: Discussionmentioning
confidence: 99%
“…Navarro et al [51] highlighted that physical self-concept, especially the perception of physical fitness, was an essential factor for enjoyment in these classes. These perceptions are important and relevant; it has even been observed that the relationships between motor skills and the practice of PA are modulated by factors such as self-concept [52][53][54][55]. Therefore, it is possible that adolescents with adequate motor skills would not agree to engage in PA, or were not fully involved, due to a distorted perception of PA.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, from a cognitive perspective, it is not yet known how the motivation and emotion experienced by adolescents in PE classes may be conditioned by the amount of extracurricular PA they perform. Recently, Zhang et al [ 42 ] highlighted that student’s ball skill competence predicted enjoyment of PA. However, they did not study whether students with high levels of ball skills were the same students with high enjoyment and level of PA.…”
Section: Introductionmentioning
confidence: 99%
“…These links become stronger across developmental periods, indicating the more motor skills a child develops, the more they prospectively engage/participate in PA. In fact, multiple school-based PA programs that target young children’s motor skill development to improve MVPA have been found to be effective (Kriemler et al, 2011 ; Lee et al, 2020a , b ; Zhang et al, 2021 ). Head Start programs need to consider integrating concepts of developing motor skills into their indoor and/or outdoor activity curricula.…”
Section: Discussionmentioning
confidence: 99%